In vitro and in vivo high-throughput assays for the testing of anti-Trypanosoma cruzi compounds. - Adriana M C Canavaci; Juan M Bustamante; Angel M Padilla; Cecilia M Perez Brandan; Laura J Simpson; Dan Xu; Courtney L Boehlke; Rick L Tarleton (Public Library of Science (PLoS), 2010)
The two available drugs for treatment of T. cruzi infection, nifurtimox and benznidazole (BZ), have potential toxic side effects and variable efficacy, contributing to their low rate of use. With scant economic resources available for antiparasitic drug discovery and development, inexpensive, high-throughput and in vivo assays to screen potential new drugs and existing compound libraries are essential.In this work, we describe the development and validation of improved methods to test anti-T. cruzi compounds in vitro and in vivo using parasite lines expressing the firefly luciferase (luc) or the tandem tomato fluorescent protein (tdTomato). For in vitro assays, the change in fluorescence intensity of tdTomato-expressing lines was measured as an indicator of parasite replication daily for 4 days and this method was used to identify compounds with IC(50) lower than that of BZ.This method was highly reproducible and had the added advantage of requiring relatively low numbers of parasites and no additional indicator reagents, enzymatic post-processes or laborious visual counting. In vivo, mice were infected in the footpads with fluorescent or bioluminescent parasites and the signal intensity was measured as a surrogate of parasite load at the site of infection before and after initiation of drug treatment. Importantly, the efficacy of various drugs as determined in this short-term (<2 weeks) assay mirrored that of a 40 day treatment course.These methods should make feasible broader and higher-throughput screening programs needed to identify potential new drugs for the treatment of T. cruzi infection and for their rapid validation in vivo.